Durability of Rubbercrete Containing Fly Ash and Nano Silica in terms of Deterioration Mechanism through Chemical Attack - Raja Abdullah, Raja Rosenani (Universiti Teknologi PETRONAS, 2017)
Several researches have been conducted to determine the properties of rubbercrete, a concrete containing crumb rubber as partial replacement to fine aggregate. The benefits of rubbercrete includes lighter in weight, more ductile, better workability, and better sound absorption. However, crumb rubber hydrophobic properties cause rubbercrete to have a lower compressive strength and durability compare to normal concrete. Therefore, Nano silica and fly ash is added into the mixture to counter this problem. This thesis presents the study of rubbercrete durability in terms of its deterioration mechanism through chemical attack. The thesis details on the effect of acid attack, sulfate attack and efflorescence to the mixture. For this work, the strength of rubbercrete is improvised by addition of Nano Silica into the mixture. Thirty trial mixes were prepared to produce concrete cubes of dimension 100 mm x 100 mm x 100 mm. The composition of rubbercrete focus on 0%, 15%, and 30% crumb rubber (CR) as replacement of fine aggregate, 0%, 2.5% and 5% addition of Nano Silica to increase its compressive strength, 0%, 35% and 70% of fly ash to replace cement and 0.25%, 0.3% and 0.35% of water-cement ratio.